Why do people volunteer for Community First Responder groups? - Vernon-Evans, Alix (2011)
Community first responders (CFRs) are being increasingly used by ambulance services in the UK to help provide emergency care in rural areas. CFRs are volunteers often with no previous medical knowledge and they have not yet been investigated sociologically. Although CFR groups work with the ambulance service, they are independently run with only basic guidelines set by the ambulance service. The motivations of lay people who join CFR groups may be significant in understanding the way in which CFR schemes are such a successful example of volunteering in the 21st century. The aim of the study is to investigate the reasons why people joined community first responder schemes. Five focus groups were carried out with five different CFR groups in Leicestershire during July 2010. Transcripts of the group discussions were then analysed using a system of coding. All participants identified having elements of altruism as a motivating factor in addition to other motivating factors such as social involvement and psychological enhancement. Participants enjoyed being part of a team of like-minded people that are able to support each other psychologically. The flexibility of CFR groups is significant, as CFRs do not feel obliged to give up their time if they do not want to and feel no resentment to the hours they do volunteer. The findings showed that the implications for volunteering in healthcare are significant. As society is moving towards a greater use of the voluntary sector in public service delivery, the way in which CFR groups work could be used as a model for other voluntary groups within the healthcare sector.